Simulationsbasierte Generierung von Präparationsrichtlinien für Zahn-Inlays im kaubelasteten Seitenzahnbereich - Klein, Daniel; Grimme, Tobias; Tremmel, Stephan; Petschelt, Anselm; Lohbauer, Ulrich; Wartzack, Sandro (ANSYS Conference & CADFEM User's Meeting 2012, 2012)
Caries is the major dental disease and the main reason for tooth extractions as clinical investigations show. Fortunately in many cases the carious lesion can be removed without extracting the whole tooth and replaced by a restoration, e.g. inlays. However, the lifetime of inlays is limited. Besides the inlay material the geomtery of the inlay can have a significant impact on the durability of an inlay. The aim of this paper is to show how the impact of the inlay geometry on the durability can be observed with the help of simulation and some common guidelines for dental restaurations are monitored.
Keywords: Simulation; Medizintechnik